Traditional marriage in Laghouat from an anthropological perspective - khineche, Ahmed; Bendjeddou, Abdelkader; Benlahbib, Sid Ahmed (Social Empowerment Journal, 2019)
Marriage is considered a sacred bond in all cultures and civilizations, and in all times and places. The rituals and preparations that accompany this deep-rooted tradition of the Laghouatian community, which we will not disagree on, differ from other regions, given the fact that Algerian society is a fertile area for cultural diversity.